ANALISIS KEMAMPUAN MENULIS PUISI SISWA DALAM MENDUKUNG SEKOLAH AKTIF LITERASI DI MTS NEGERI 1 PATI - Rohmah, Iffatur; Budi Santosa, Achadi; Hidayati, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students’ poetry writing skills in supporting the Active Literacy School Program at MTs Negeri 1 Pati. The research employed a qualitative method with a descriptive approach. The research subjects included Indonesian language teachers, the literacy coordinator, and students of MTs Negeri 1 Pati. Data were collected through participatory observation, in-depth interviews, and documentation of students’ poetry works. Data analysis was conducted qualitatively through data reduction, data display, and conclusion drawing, assisted by ATLAS.ti software for systematic coding and thematic mapping. The findings indicate that students’ poetry writing skills consist of several interrelated aspects, including theme selection based on personal experience, thematic coherence, the ability to construct imagery, mastery of figurative language, and the ability to convey messages or moral values. In general, students are able to select themes related to their personal experiences and interests, maintain consistency between theme and content, and begin to develop imagery through language involving imagination and sensory perception. However, students’ mastery of diction and figurative language varies. The Active Literacy School Program plays a significant role in supporting students’ poetry writing skills through structured literacy activities, such as literacy hours, reading habituation, creative writing activities, and the publication of students’ works. Nevertheless, challenges remain, including differences in students’ interests, limited vocabulary, and constrained instructional time. This study concludes that the Active Literacy School Program contributes positively to the development of students’ poetry writing skills, although continuous guidance is still needed to enhance linguistic quality and aesthetic aspects.